High-reflection black packaging adhesive film, preparation method thereof and LECO battery single-glass assembly

By using a highly reflective black packaging film in the single glass LECO battery assembly, combined with modified hollow glass microbeads and modified POE resin, the components' anti-humidity and heat aging performance and full black appearance are solved, and efficient and economical component performance improvement is achieved.

CN119698077APending Publication Date: 2025-03-25JIANGSU LUSHAN PHOTOVOLTAIC TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411822112.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent anti-humidity and heat aging performance and a full black appearance in LECO battery single glass components.

Method used

A highly reflective black encapsulated film is used, which consists of a black layer and a white layer. Modified hollow glass microbead masterbatch is introduced into the black layer. Modified POE resin is used in the white layer. Through the acid adsorption effect of the modified hollow glass microbeads and the crosslinking network of the modified POE resin, the film's anti-humidity and heat aging performance is improved.

Benefits of technology

It realizes the excellent anti-humidity and heat aging performance and full black appearance of the single glass LECO battery, while reducing production costs and processing difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183337670000161
    Figure BDA0005183337670000161
  • Figure BDA0005183337670000171
    Figure BDA0005183337670000171
  • Figure BDA0005183337670000181
    Figure BDA0005183337670000181
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic adhesive films, in particular to a high-reflection black packaging adhesive film, a preparation method of the high-reflection black packaging adhesive film and an LECO battery single-glass assembly. The high-reflection black packaging adhesive film comprises a black layer and a white layer, the black layer is prepared from the following components in parts by weight: 60 to 80 parts of EVA (Ethylene Vinyl Acetate) resin, 10 to 30 parts of black master batch, 5 to 20 parts of modified hollow glass bead master batch and 0.7 to 3.4 parts of first aid; the modified hollow glass beads are hollow glass beads with surfaces modified by silane coupling agents; the white layer is prepared from the following components in parts by weight: 45 to 75 parts of EVA (Ethylene Vinyl Acetate) resin, 10 to 30 parts of modified POE (Polyolefin Elastomer) resin, 15 to 25 parts of white master batch and 0.7 to 3.4 parts of second aid. The high-reflection black packaging adhesive film provided by the invention is suitable for LECO battery single-glass assemblies, and has excellent damp-heat aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic adhesive films, and in particular to a highly reflective black packaging adhesive film and a preparation method thereof, and a LECO battery single-glass component. Background Art

[0002] In the development history of photovoltaic cells, improving efficiency has always been one of the goals pursued by researchers. For TOPCon cells, the structural design requires finding a balance between the surface passivation layer and the metal contact in order to reduce the recombination of electron-hole pairs while maintaining good current collection. Traditional TOPCon cells use silver-aluminum paste as a conductive adhesive, and the presence of aluminum will accelerate the corrosion of the cell. To prevent this phenomenon, a more corrosion-resistant packaging material, such as polyolefin elastomer (POE) film, is usually used to protect the cell from moisture and oxygen. The emergence of LECO technology allows high-quality metal contact points to be achieved without compromising the properties of the passivation layer. It can locally destroy the passivation layer in a very precise way and promote electron transfer between metal and silicon. After using pure silver paste, the corrosion problem caused by aluminum no longer exists, so the ethylene-vinyl acetate copolymer (EVA) film, which is lower in cost and easier to process, can be selected for packaging, which requires higher resistance to moisture and heat aging of the film itself.

[0003] Conventional TOPCon black modules generally use double-glass packaging, with EPE film on the front film and black EVA film on the back film. Double-glass modules have strong water vapor barrier properties, limited water vapor intrusion paths, and are not easy to form a humid and acidic environment. Therefore, this combination has excellent anti-PID and anti-wet heat aging properties. However, the general installation environment of black modules is distributed rooftop power generation and photovoltaic building integration, which has higher requirements for lightweight modules. Single-glass modules are light in weight, and single-glass modules can save manpower, transportation and other systemic costs. They are particularly suitable for installation in sites with high weight requirements, especially for installation on traditional roofs, and the production and installation costs are relatively low; but the anti-wet heat aging performance of single-glass modules is significantly weaker than that of double-glass modules. Therefore, it is of great significance to develop a high-reflection black packaging film suitable for LECO battery single-glass modules with excellent anti-wet heat aging performance.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a highly reflective black encapsulation film that can be used to prepare a LECO battery single-glass component, which not only has excellent resistance to moisture and heat aging and PID performance, but also can achieve a completely black appearance.

[0006] Another object of the present invention is to provide a method for preparing a highly reflective black packaging film.

[0007] Another object of the present invention is to provide a LECO cell single-glass component, comprising the above-mentioned high-reflective black packaging film.

[0008] In order to achieve the above-mentioned object of the present invention, the present invention provides a highly reflective black packaging film on one hand, comprising a black layer and a white layer;

[0009] The black layer comprises the following components by weight: 60-80 parts of EVA resin, 10-30 parts of black masterbatch, 5-20 parts of modified hollow glass microbead masterbatch and 0.7-3.4 parts of the first auxiliary agent; the modified hollow glass microbead is a hollow glass microbead modified by a surface silane coupling agent;

[0010] The white layer comprises the following components in parts by weight: 45 to 75 parts of EVA resin, 10 to 30 parts of modified POE resin, 15 to 25 parts of white masterbatch and 0.7 to 3.4 parts of a second auxiliary agent.

[0011] In a specific embodiment of the present invention, the modified hollow glass microsphere masterbatch is mainly prepared by extrusion granulation of 80-95 parts of EVA resin, 0.01-0.1 parts of initiator and 5-20 parts of modified hollow glass microspheres by weight.

[0012] In a specific embodiment of the present invention, the preparation of the modified hollow glass microspheres includes: the hollow glass microspheres react in an ethanol solution of a silane coupling agent and then dry the hollow glass microspheres. Further, in the ethanol solution of the silane coupling agent, the concentration of the silane coupling agent is 1wt% to 10wt%.

[0013] In a specific embodiment of the present invention, the particle size of the hollow glass microspheres is 5 to 30 μm, and the true density of the hollow glass microspheres is 0.5 to 2 g / cm 3 .

[0014] In a specific embodiment of the present invention, the silane coupling agent in the modified hollow glass microspheres includes at least one of KH550, KH560, KH570, KH580 and KH591.

[0015] In a specific embodiment of the present invention, the melt index of the EVA resin is 5 to 25 g / 10 min, and the VA content of the EVA resin is ≥ 25 wt%.

[0016] In a specific embodiment of the present invention, the modified POE resin is mainly prepared by extrusion granulation of 100 parts of POE resin, 0.01-0.1 parts of initiator and 0.1-2 parts of silane coupling agent in parts by weight.

[0017] In a specific embodiment of the present invention, the melt index of the POE resin is 2 to 30 g / 10 min, and the α-olefin content in the POE resin is 0% to 45%.

[0018] In a specific embodiment of the present invention, the first auxiliary agent and the second auxiliary agent each independently include the following components in parts by weight: 0.4-1 part of a peroxide crosslinking agent, 0.2-0.8 part of a co-crosslinking agent, 0.1-1 part of a silane coupling agent, 0-0.3 part of a light stabilizer and 0-0.3 part of an antioxidant.

[0019] In a specific embodiment of the present invention, the ratio of the thickness of the black layer to the thickness of the white layer is 1:(0.8-1.2).

[0020] Another aspect of the present invention provides a method for preparing any one of the above-mentioned highly reflective black packaging adhesive films, comprising the following steps: preparing materials according to the components of the black layer and the white layer, and performing extrusion and casting to form a film.

[0021] Another aspect of the present invention provides a LECO battery single-glass component, comprising any one of the above-mentioned high-reflective black packaging films.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) In the highly reflective black encapsulation film of the present invention, modified hollow glass microbead masterbatch is introduced into the black layer. The hollow glass microbead has a certain adsorption effect on acid, thereby preventing acidic substances from corroding the battery cell and improving the reliability of the component under a damp and hot aging environment; and in the long-term damp and hot aging process, the interface bonding force between the glass microbead and the resin phase can be improved to avoid aging and delamination;

[0024] (2) The present invention uses a silane coupling agent to modify the hollow glass microspheres, thereby avoiding the consumption of silane in the black layer by the silanol groups of the hollow glass microspheres and improving the compatibility of the hollow glass microspheres with the EVA resin;

[0025] (3) In the white layer of the present invention, a modified POE resin is used to improve the compatibility of the POE resin and the EVA resin. During the high-temperature lamination process, the modified POE resin can be quickly cross-linked with the EVA resin to construct a denser cross-linking network, further improving the anti-wet heat aging performance;

[0026] (4) The highly reflective black encapsulation film of the present invention is suitable for LECO battery single-glass modules. Fillers are added to the black layer and the white layer respectively, and a low melt index resin is used to reduce fluidity. Without electron beam irradiation, it can fully meet the requirement of no glue overflow after lamination, and can effectively improve the peel strength. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] In existing highly reflective black packaging films, alkaline fillers are usually introduced into the films to improve the wet-heat aging performance. However, the introduction of alkaline fillers will weaken the black color, resulting in reduced reflectivity. If other layers are stacked and alkaline fillers are introduced into the other layers, the bonding performance between the layers cannot be effectively guaranteed.

[0029] Based on this, the present invention provides a highly reflective black packaging film, including a black layer and a white layer;

[0030] The black layer includes the following components by weight: 60-80 parts of EVA resin, 10-30 parts of black masterbatch, 5-20 parts of modified hollow glass microbead masterbatch and 0.7-3.4 parts of the first auxiliary agent; the modified hollow glass microbead is a hollow glass microbead modified by a surface silane coupling agent;

[0031] The white layer includes the following components in parts by weight: 45-75 parts of EVA resin, 10-30 parts of modified POE resin, 15-25 parts of white masterbatch and 0.7-3.4 parts of the second auxiliary agent.

[0032] The encapsulation film of the present invention is provided with a black layer and a white layer, and a modified hollow glass microbead masterbatch is introduced into the black layer. The hollow glass microbead is a kind of soda lime borate glass. The hollow glass microbeads utilize the acid adsorption effect on acid to avoid acidic substances from corroding the battery cell, thereby improving the reliability of the assembly in a wet and hot aging environment. At the same time, during the long-term wet and hot aging process, the acidic substances released by the EVA resin will corrode the surface of the hollow glass microbeads, exposing the hollow surface. On the one hand, the polymer chain segments of the resin can enter the glass microbeads; on the other hand, a large number of silanol groups are formed on the surface of the corroded glass microbeads, which can improve the interface bonding force between the glass microbeads and the resin phases, and avoid the occurrence of aging delamination.

[0033] The white layer is made of EVA resin and modified POE resin. POE resin can improve the poor water vapor barrier and poor anti-wet heat aging performance of EVA resin. Moreover, the introduction of EVA resin can further improve the bonding performance between the white layer and the black layer. Moreover, the additives in the white layer, such as silane coupling agent, can chemically bond with the modified hollow glass microbeads in the black layer during the lamination process, further improving the interface bonding performance.

[0034] For example, in different embodiments, in the black layer, the amounts of the components in parts by weight may be as follows:

[0035] The amount of EVA resin can be 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts or a range consisting of any two of them;

[0036] The amount of black masterbatch can be 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts or a range consisting of any two of them;

[0037] The dosage of the modified hollow glass microbead masterbatch can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts or any two of them; the study found that the dosage of the modified hollow glass microbead masterbatch has a great influence on the tensile strength and color value of the encapsulation film; when the dosage of the modified hollow glass microbead masterbatch is too large, the tensile strength of the encapsulation film is reduced and the black color value is affected; when the dosage of the modified hollow glass microbead masterbatch is too small, the improvement of the anti-wet heat aging performance cannot be achieved;

[0038] The dosage of the first auxiliary agent can be 0.7 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.4 parts or a range consisting of any two of them.

[0039] For example, in different embodiments, in the white layer, the amounts of each component in parts by weight may be as follows:

[0040] The amount of EVA resin can be 45 parts, 50 parts, 55 parts, 60 parts, 70 parts, 75 parts or a range consisting of any two of them;

[0041] The amount of the modified POE resin can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or a range consisting of any two of them;

[0042] The amount of white masterbatch can be 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or any two of them;

[0043] The dosage of the second auxiliary agent can be 0.7 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.4 parts or a range consisting of any two of them.

[0044] The present invention further studies and finds that in the white layer, when the mass ratio of EVA resin to modified POE resin is (2-4) : 1, it is more helpful to balance the water vapor permeability of the encapsulation film as a whole, and ensure the compatibility of the white layer and the black layer, improve the tensile properties, and avoid component degradation problems caused by bubbles during the lamination process. For example, in different implementations, in the white layer, the mass ratio of EVA resin to modified POE resin can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or a range consisting of any two of them. When the amount of EVA resin in the white layer is too high and exceeds the above range, when used in a single-glass TOPCon encapsulation system, there is a probability that the reliability will not be up to standard.

[0045] In a specific embodiment of the present invention, the modified hollow glass microsphere masterbatch is mainly prepared by extrusion granulation of 80-95 parts of EVA resin, 0.01-0.1 parts of initiator and 5-20 parts of modified hollow glass microspheres by weight.

[0046] For example, in different embodiments, the amounts of the components used to prepare the modified hollow glass microbead masterbatch can be as follows, measured by weight:

[0047] The amount of EVA resin can be 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts or any two of them; the type of EVA resin can be the same as the EVA resin used in the black layer;

[0048] The amount of the initiator can be 0.01 part, 0.03 part, 0.05 part, 0.08 part, 0.1 part or any two of them; the initiator can be selected from at least one of dicarbonate peroxide, acyl peroxide and ester peroxide;

[0049] The amount of the modified hollow glass microspheres can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts or a range consisting of any two of them.

[0050] In a specific embodiment of the present invention, the modified hollow glass microsphere masterbatch is mainly prepared by extrusion granulation of 90-95 parts of EVA resin, 0.01-0.05 parts of initiator and 5-10 parts of modified hollow glass microspheres by weight.

[0051] In actual operation, the aspect ratio of the twin screw used for extrusion granulation can be (7-40) : 1, such as (16-25) : 1.

[0052] In a specific embodiment of the present invention, in the preparation of the modified hollow glass microbead masterbatch, the temperature of the extrusion granulation is 110 to 160°C, preferably 130 to 160°C.

[0053] In a specific embodiment of the present invention, the preparation of the modified hollow glass microspheres includes: the hollow glass microspheres react in an ethanol solution of a silane coupling agent and then dry the hollow glass microspheres. Further, in the ethanol solution of the silane coupling agent, the concentration of the silane coupling agent is 1wt% to 10wt%.

[0054] In actual operation, the hollow glass microspheres can be placed in an ethanol solution of a silane coupling agent, the solution can be immersed in the hollow glass microspheres, mechanically stirred at room temperature for more than 2 hours, filtered, placed in a vacuum drying oven, and dried at 100 to 105° C. for more than 4 hours to obtain modified hollow glass microspheres. For example, in different embodiments, the concentration of the silane coupling agent in the ethanol solution of the silane coupling agent can be 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, preferably 3wt% to 5wt%.

[0055] In a specific embodiment of the present invention, the amount of the ethanol solution of the silane coupling agent is 1.5 to 3 times the mass of the hollow glass microspheres, such as 2 times but not limited thereto.

[0056] In a specific embodiment of the present invention, the average particle size of the hollow glass microspheres is 5 to 30 μm, and the true density of the hollow glass microspheres is 0.5 to 2 g / cm 3 .

[0057] For example, in different embodiments, the particle size of the hollow glass microspheres can be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any two of them, preferably 5 to 10 μm; the true density of the hollow glass microspheres can be 0.5 g / cm 3 , 1g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 , 2g / cm 3 Or the range of any two of them, preferably 1.5 to 2 g / cm 3 .

[0058] In a specific embodiment of the present invention, the silane coupling agent in the modified hollow glass microspheres includes at least one of KH550, KH560, KH570, KH580 and KH591.

[0059] In a specific embodiment of the present invention, the modified POE resin is mainly prepared by extrusion granulation of 100 parts of POE resin, 0.01-0.1 parts of initiator and 0.1-2 parts of silane coupling agent by weight. Further, the extrusion granulation temperature is 130-170°C.

[0060] Due to the poor compatibility of POE resin and EVA resin, simple melt blending can easily lead to the problem of low tensile strength of the film. The present invention adopts a silane coupling agent to graft-modify the POE resin, increase the polarity of POE, improve its compatibility with the EVA resin, and enhance the tensile strength of the film. For example, in different embodiments, in the modified POE resin, compared to 100 parts by weight of POE resin, the amount of the silane coupling agent can be 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts or any two of them.

[0061] In actual operation, the silane coupling agent used to prepare the modified POE resin may contain at least one of a double bond, an epoxy group, an amino group, a urea group and a thiol group. The initiator used to prepare the modified POE resin includes at least one of a dicarbonate peroxide, an acyl peroxide and an ester peroxide.

[0062] In a specific embodiment of the present invention, the EVA resin used in the white layer and the black layer respectively meets the following requirements: the melt index of the EVA resin is 5-25 g / 10 min, and the VA content of the EVA resin is ≥25 wt %. Furthermore, the volume resistivity of the EVA resin is >1×10 14 Ω·cm.

[0063] For example, in different embodiments, the melt index of the EVA resin can be 5g / 10min, 8g / 10min, 10g / 10min, 12g / 10min, 15g / 10min, 20g / 10min, 25g / 10min or a range composed of any two of them, preferably 5-8g / 10min. The VA content of the EVA resin can be 25wt%, 28wt%, 29wt%, 30wt%, such as 26wt%-30wt%. The present invention adopts an EVA resin with a low melt index, combined with the composition of the black layer and the white layer, which can meet the requirement of no glue overflow after lamination without electron beam irradiation and improve the peel strength.

[0064] In a specific embodiment of the present invention, the melt index of the POE resin is 2 to 30 g / 10 min, and the α-olefin content in the POE resin is 0% to 45%. Furthermore, the volume resistivity of the POE resin is greater than 1×10 14 Ω·cm.

[0065] For example, in different embodiments, the melt index of the POE resin can be 2g / 10min, 5g / 10min, 8g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, 30g / 10min or a range composed of any two of them, preferably 3 to 8g / 10min. The α-olefin content in the POE resin can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, such as 20% to 30%. The present invention adopts EVA resin with a low melt index, combined with the composition of the black layer and the white layer, which can meet the requirement of no glue overflow after lamination without electron beam irradiation and improve the peel strength.

[0066] In a specific embodiment of the present invention, the black pigment in the black masterbatch includes at least one of carbon black, iron chrome black, cobalt black, copper chrome black, aniline black, antimony sulfide, manganese iron black and benzene series.

[0067] In a specific embodiment of the present invention, the white pigment in the white masterbatch includes at least one of titanium dioxide, silicon dioxide, zinc oxide, zinc sulfide and barium sulfate, and is preferably rutile nano-grade titanium dioxide.

[0068] In a specific embodiment of the present invention, the first auxiliary agent and the second auxiliary agent each independently include the following components in parts by weight: 0.4-1 part of a peroxide crosslinking agent, 0.2-0.8 part of a co-crosslinking agent, 0.1-1 part of a silane coupling agent, 0-0.3 part of a light stabilizer and 0-0.3 part of an antioxidant.

[0069] Among them, the peroxide crosslinking agent may include at least one of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, peroxy-2-ethylhexyl carbonate tert-butyl ester and peroxy-2-ethylhexyl carbonate tert-amyl ester; the auxiliary crosslinking agent may include at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and diallyl phthalate; the silane coupling agent may include 3-glycidyloxypropylmethyldiethoxysilane, 3-glycidyloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, , 3-aminopropyltriethoxysilane, 3-ureapropyltrialkoxysilane and 3-mercaptopropyltrimethoxysilane; the light stabilizer may include at least one of phenyl salicylate, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2-hydroxy-5-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester; the antioxidant may include at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite and 2,6-di-tert-butyl-4-methylphenol and distearyl thiodipropionate and phosphite.

[0070] In a specific embodiment of the present invention, the thickness ratio of the black layer to the white layer is 1:(0.8-1.2). For example, in different embodiments, the thickness ratio of the black layer to the white layer can be 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2 or a range consisting of any two of them.

[0071] The overall thickness of the high-reflective black packaging film of the present invention can be freely selected according to actual needs. For example, the film weight of the high-reflective black packaging film of the present invention can be 400-500 g / m 2 , but not limited to this.

[0072] In a specific embodiment of the present invention, the reflectivity of the high-reflective black packaging film in the wavelength range of 780-1100 nm is ≥80%.

[0073] Another aspect of the present invention provides a method for preparing any one of the above-mentioned highly reflective black packaging films, comprising the following steps: respectively preparing the components of the black layer and the white layer, and performing extrusion and casting to form a film. The temperature of the casting film can be 100±10°C, which can be conventionally adjusted according to the component preparation.

[0074] In a specific embodiment of the present invention, the preparation of the highly reflective black packaging adhesive film does not include an electron beam irradiation step.

[0075] Another aspect of the present invention provides a LECO battery single-glass component, comprising any one of the above-mentioned high-reflective black packaging films.

[0076] Example 1

[0077] This embodiment provides a highly reflective black packaging film, including a black layer and a white layer stacked in a thickness ratio of 1:1, and a film weight of 450g / m 2 .

[0078] The black layer includes the following components by weight: 70 parts of EVA resin, 25 parts of black masterbatch, 5 parts of modified hollow glass microbead masterbatch, 1 part of peroxide crosslinking agent, 0.8 parts of auxiliary crosslinking agent, 0.7 parts of silane coupling agent, 0.1 parts of light stabilizer and 0.1 parts of antioxidant.

[0079] The preparation of modified hollow glass microsphere masterbatch includes: weighing 8 parts of modified hollow glass microspheres, 92 parts of EVA resin, and 0.01 parts of initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane by weight, mixing and extruding in a twin-screw extruder with a length-to-diameter ratio of 16:1, and the grinding head extrusion temperature is 140°C. The preparation of modified hollow glass microspheres includes: immersing the hollow glass microspheres in a 4% silane coupling agent ethanol solution (the solution immerses the hollow glass microspheres, and the mass of the solution is about twice the mass of the hollow glass microspheres), mechanically stirring for 2 hours, filtering, and placing in a vacuum drying oven at 105°C for 4 hours. The average particle size of the hollow glass microspheres is 5μm, and the true density is 1.5g / cm 3 .

[0080] The white layer includes the following components in parts by weight: 60 parts of EVA resin, 20 parts of modified POE resin, 20 parts of white masterbatch, 1 part of peroxide crosslinking agent, 0.8 parts of auxiliary crosslinking agent, 0.6 parts of silane coupling agent, 0.1 parts of light stabilizer and 0.1 parts of antioxidant.

[0081] The preparation of the modified POE resin includes: weighing 100 parts of POE resin, 0.05 parts of initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 0.8 parts of silane coupling agent KH550 by weight, mixing and extruding in a twin-screw extruder with a length-to-diameter ratio of 16:1, and the extrusion temperature is 160°C.

[0082] Among the above materials, the melt index of EVA resin is 8g / 10min, and the VA content is 28wt%; the black masterbatch is made of conventional infrared transparent black pigment and EVA resin (Sailbon V2825) in a mass ratio of 20:80, and a twin-screw extruder with a length-to-diameter ratio of 40:1 is used to extrude and granulate at 140°C; the white masterbatch is made of conventional high-reflective white pigment and EVA resin (Sailbon V2825) in a mass ratio of 40:60, and a twin-screw extruder with a length-to-diameter ratio of 40:1 is used to granulate at 140°C; the melt index of POE resin is 6g / 10min, and the α-olefin content is 25wt%. The peroxide crosslinking agent is 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, the auxiliary crosslinking agent is trimethylolpropane triacrylate, the silane coupling agent is 3-glycidyloxypropylmethyldiethoxysilane, the light stabilizer is 2-hydroxy-4-methoxybenzophenone, and the antioxidant is pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0083] The preparation method of the highly reflective black packaging film of this embodiment includes the following steps: respectively preparing the ingredients of the black layer and the white layer, and sealing and drying them in a 55°C forced air drying oven, and then casting them on an extruder at 100°C to obtain a highly reflective black packaging film.

[0084] Example 2

[0085] This embodiment refers to the high-reflective black packaging film and its preparation method of Example 1, and the only difference is that the amounts of EVA resin, black masterbatch, and modified hollow glass microbead masterbatch in the black layer are different.

[0086] In this embodiment, the amount of EVA resin used is 66.5 parts by weight, the amount of black masterbatch used is 23.5 parts by weight, and the amount of modified hollow glass microbead masterbatch used is 10 parts by weight.

[0087] Example 3

[0088] This embodiment refers to the high-reflective black packaging film and its preparation method of Example 1, and the only difference is that the amounts of EVA resin, black masterbatch, and modified hollow glass microbead masterbatch in the black layer are different.

[0089] In this embodiment, the amount of EVA resin used is 60 parts by weight, the amount of black masterbatch used is 20 parts by weight, and the amount of modified hollow glass microbead masterbatch used is 20 parts by weight.

[0090] Example 4

[0091] This embodiment refers to the high-reflective black packaging adhesive film and preparation method thereof of Embodiment 1, with the only difference being that the amounts of the EVA resin and the modified POE resin in the white layer are different.

[0092] In this embodiment, the amount of EVA resin in the white layer is 50 parts by weight, and the amount of modified POE resin is 30 parts by weight.

[0093] Example 5

[0094] This embodiment refers to the high-reflective black packaging adhesive film and preparation method thereof of Embodiment 1, with the only difference being that the types of EVA resin and POE resin are different.

[0095] In this embodiment, the melt index of the EVA resin is 15 g / 10 min, and the VA content is 28 wt %; the melt index of the POE resin is 15 g / 10 min, and the α-olefin content is 25 wt %.

[0096] Example 6

[0097] This embodiment refers to the high-reflective black packaging adhesive film and its preparation method of Embodiment 5, and the only difference is that the preparation method of the high-reflective black packaging adhesive film is different.

[0098] In this embodiment, in the preparation of the highly reflective black packaging adhesive film, after the film is cast, it is irradiated at a voltage of 500 KV, a line speed of 15 m / min, and a beam current of 30 mA to obtain the highly reflective black packaging adhesive film.

[0099] Comparative Example 1

[0100] Comparative Example 1 refers to the high-reflective black packaging film and its preparation method of Example 1, except that: the amounts of EVA resin and modified POE resin in the white layer are different.

[0101] In Comparative Example 1, the amount of EVA resin in the white layer is 40 parts by weight, and the amount of modified POE resin is 40 parts by weight.

[0102] Comparative Example 2

[0103] Comparative Example 2 refers to the high-reflective black packaging film and its preparation method of Example 1, except that: the white layer does not include modified POE resin, the missing amount of modified POE resin is supplemented by EVA resin, and the rest remains unchanged.

[0104] In Comparative Example 2, the amount of EVA resin in the white layer is 80 parts by weight, and the amount of modified POE resin is 0.

[0105] Comparative Example 3

[0106] Comparative Example 3 refers to the high-reflective black packaging film and its preparation method of Example 1, except that: an equal amount of POE resin is used in the white layer to replace the EVA resin and the modified POE resin, and the rest remains unchanged.

[0107] In Comparative Example 3, the amount of POE resin in the white layer is 80 parts by weight.

[0108] Comparative Example 4

[0109] Comparative Example 4 refers to the high-reflective black packaging film and its preparation method of Example 1, except that an equal amount of POE resin is used in the white layer to replace the modified POE resin, and the rest remains unchanged.

[0110] In Comparative Example 4, the amount of EVA resin in the white layer is 60 parts by weight, and the amount of POE resin is 20 parts by weight.

[0111] Comparative Example 5

[0112] Comparative Example 5 refers to the high-reflective black packaging film and its preparation method of Example 1, except that the amounts of EVA resin, black masterbatch and modified hollow glass microbead masterbatch in the black layer are different.

[0113] In Comparative Example 5, the amount of EVA resin used is 73.7 parts by weight, the amount of black masterbatch used is 26.3 parts by weight, and the amount of modified hollow glass microbead masterbatch used is changed to 0.

[0114] Experimental example

[0115] The encapsulation films prepared in different embodiments and comparative examples were subjected to the following tests, and the test results are shown in Table 1.

[0116] Reflectivity test: Take a 100mm*100mm encapsulation film sample and put it into a laminator at 145℃, take it out after 15 minutes, cool it down, cut it into 30mm*50mm small pieces, put it into a UV-visible spectrophotometer to test the reflectivity in the range of 780~1100nm;

[0117] Peel strength test: Take two pieces of 300mm*300mm packaging film, stack them in the order of glass / packaging film (two pieces) / CPC backplane, put them into a vacuum laminator, press at 145℃ for 15 minutes, take them out and let them stand to room temperature; in the width direction, cut the CPC backplane / packaging film layer into samples with a width of 10mm±0.5mm every 5mm, and perform peel strength test at a tensile speed of 100±10mm / min;

[0118] Tensile strength and elongation at break test: Lamination at 145°C for 15 minutes, cooling to room temperature, sample shape and size are cut from large samples according to the provisions of Type 5 test in GB / T 1040.3-2006, and 5 samples are prepared for each group. The sample thickness d is recorded with a micrometer, and the tensile test is carried out on a tensile testing machine at a speed of 100±10mm / min;

[0119] Vulcanization value test: Take several pieces of 30mm*30mm packaging film, weigh them to 5±0.5g, place them in a stack between two 15μm release films, vulcanize at 145℃ for 15min, and record the vulcanization ML value;

[0120] Acid value test: Take a 300mm*300mm encapsulation film sample and put it into a laminator at 145℃. Take it out after 15 minutes. After cooling, cut it into 3mm*3mm small pieces. Accurately weigh 8g of the sample and place it in a conical flask for airtight storage; prepare a mixture of distilled water and anhydrous ethanol in a volume ratio of 1:1, take 110mL of the mixture and pour it into the conical flask with the sample, use ultrasonic wave with a frequency of 40KHz for 30 minutes, temperature 25-28℃, ultrasonic wave for 30 minutes; use a 100mL constant volume flask to calibrate Pipette 100mL of ultrasonically treated extraction solution into a titration bottle, add 10 drops of prepared bromothymol blue indicator. At this moment, the solution in the bottle is a light yellow solution. Titrate with KOH-ethanol standard solution to a cyan or light blue endpoint, and record the required volume of KOH solution V1. Use 100mL of a mixture of distilled water and anhydrous ethanol for a blank test, add the same amount of indicator solution, and titrate to the same color change endpoint, and record the required volume of KOH solution V2. Calculate the acid value according to the following formula:

[0121]

[0122] Water vapor transmission rate test: Take a 300mm*300mm packaging film sample and put it into a laminator at 145℃, take it out after 15 minutes, cool it down, and cut the film into discs with a radius of 100mm with a standard cutter; put it into a water vapor transmission instrument, set the parameters to 38℃ temperature and 90% humidity, conduct the test, and record the water vapor transmission rate data;

[0123] Power attenuation rate test: 182mm TOPCon cells are connected in series according to 4*16 half cells, and laminated at 145℃ for 15min to form a photovoltaic module with no defects in appearance according to glass-transparent film-cell-high-reflective black encapsulation film-CPC backplane. Calibrate according to the enterprise standard components and test the sample power (recorded as P1). Put it in a high temperature and high humidity aging box with a temperature of 85±5℃ and a humidity of 85±5%, connect the PID power supply -1500V, power on the component, and test the sample power after 192h (recorded as P2).

[0124] Power attenuation rate = (P1-P2) / P1*100%.

[0125] DH1000h appearance test: visual inspection.

[0126] Table 1 Performance test results of different encapsulation films

[0127]

[0128]

[0129] Note: Since the chromaticity value (L value) of the black layer of the encapsulation film of Example 3 is significantly higher than that of Examples 1 and 2, no further tests are performed.

[0130] From the above test results, it can be seen from Example 1, Example 4, and Comparative Examples 1 to Comparative Examples 3 that as the amount of modified POE resin added in the white layer increases, the water vapor permeability of the encapsulation film gradually decreases, but when the amount of modified POE resin added is more, although the POE resin is modified, the polarity difference between it and EVA is also relatively large, and the compatibility with EVA is also limited. Too much modified POE resin causes the tensile strength of the encapsulation film to be significantly reduced, and the requirement of tensile strength>16MPa cannot be met. In Comparative Example 3, pure POE resin is used as the base resin of the white layer. During the initial test, there will be no abnormalities in appearance and performance, but during the long-term wet heat aging test, snowflake-like delamination will slowly appear at the four corners and edges; the longer the aging time, the single-glass component uses a backplane, and water vapor can easily invade from the outside of the component to the inside of the component, and the delamination range will expand to the inside of the component, seriously affecting the appearance and reliability of the component.

[0131] In Comparative Example 4, the POE resin was not modified. Although the initial performance was not much different from that of the embodiment, there was a probability of bubbles and other problems during the lamination of the components, which seriously affected the appearance and reliability of the components and caused the components to be degraded. This is because the EVA resin and the POE resin in the white layer were only melt-blended during the casting process. After high-temperature lamination, a denser cross-linked network could not be formed. On the contrary, due to the difference in vulcanization speed between the EVA resin and the POE resin, bubbles were easily generated during the lamination process.

[0132] The difference between Examples 1 to 2 and Comparative Example 5 is mainly that the amount of modified hollow glass microbead masterbatch in the black layer is different. From the acid value data, it can be seen that the acid value of the encapsulation film of Comparative Example 5 is significantly higher than that of the other examples; from the power attenuation data of DH1000h, it can also be seen that the power attenuation cannot meet the requirement of <5% without adding modified hollow glass microbead masterbatch in Comparative Example 5. The lower the acid value, the more effectively it can reduce the production of acetic acid in EVA and reduce the corrosion of the battery. It has a super-long component protection function and can protect photovoltaic components to achieve long-term high-reliability operation in a hot and humid environment. The amount of modified hollow glass microbead masterbatch in the black layer of Example 3 is further increased compared with Example 2, the chromaticity value (L value) of the black layer increases, and the blackness decreases. When the amount of modified hollow glass microbead masterbatch is further increased, the tensile strength will be greatly reduced, and the chromaticity value of the black layer will also be affected, affecting the appearance of the component.

[0133] Compared with Example 1, the melt index of the EVA resin and POE resin used in Example 5 is high. After lamination, the black layer and the white layer will interpenetrate each other, which seriously affects the appearance of the component.

[0134] Compared with Example 1, the melt index of the EVA resin and POE resin used in Example 6 is high, and after electron beam irradiation, there is no problem with the lamination appearance, but the peel strength is significantly lower than that of Example 1. In addition, Example 6 needs to go through the process of rewinding and packaging after casting after electron beam irradiation, which increases the risk of product quality of the film and increases the cost.

[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Highly reflective black packaging film, characterized in that: Includes black layer and white layer; The black layer comprises the following components by weight: 60-80 parts of EVA resin, 10-30 parts of black masterbatch, 5-20 parts of modified hollow glass microbead masterbatch and 0.7-3.4 parts of the first auxiliary agent; the modified hollow glass microbead is a hollow glass microbead modified by a surface silane coupling agent; The white layer comprises the following components in parts by weight: 45 to 75 parts of EVA resin, 10 to 30 parts of modified POE resin, 15 to 25 parts of white masterbatch and 0.7 to 3.4 parts of a second auxiliary agent.

2. The highly reflective black packaging film according to claim 1, characterized in that: The modified hollow glass microbead masterbatch is mainly prepared by extrusion granulation of 80-95 parts of EVA resin, 0.01-0.1 parts of initiator and 5-20 parts of modified hollow glass microbeads by weight.

3. The highly reflective black packaging film according to claim 2, characterized in that: The preparation of the modified hollow glass microspheres comprises: reacting the hollow glass microspheres in an ethanol solution of a silane coupling agent and then drying the solution; Preferably, in the ethanol solution of the silane coupling agent, the concentration of the silane coupling agent is 1 wt % to 10 wt %.

4. The highly reflective black packaging film according to claim 3, characterized in that: The particle size of the hollow glass microspheres is 5 to 30 μm, and the true density of the hollow glass microspheres is 0.5 to 2 g / cm 3 ; Preferably, the silane coupling agent in the modified hollow glass microspheres includes at least one of KH550, KH560, KH570, KH580 and KH591.

5. The highly reflective black packaging film according to claim 1, characterized in that: The melt index of the EVA resin is 5-25 g / 10 min, and the VA content of the EVA resin is ≥25 wt %.

6. The highly reflective black packaging film according to claim 1, characterized in that: The modified POE resin is mainly prepared by extrusion granulation of 100 parts of POE resin, 0.01-0.1 parts of initiator and 0.1-2 parts of silane coupling agent by weight; Preferably, the melt index of the POE resin is 2 to 30 g / 10 min, and the α-olefin content in the POE resin is 0% to 45%.

7. The highly reflective black packaging film according to claim 1, characterized in that: The first auxiliary agent and the second auxiliary agent each independently include the following components in parts by weight: 0.4-1 part of a peroxide crosslinking agent, 0.2-0.8 part of a co-crosslinking agent, 0.1-1 part of a silane coupling agent, 0-0.3 part of a light stabilizer and 0-0.3 part of an antioxidant.

8. The highly reflective black packaging film according to claim 1, characterized in that: The thickness ratio of the black layer to the white layer is 1:(0.8-1.2).

9. A method for preparing a highly reflective black packaging film, characterized in that: The method comprises the following steps: respectively preparing the components of the black layer and the white layer of the high-reflective black packaging film according to any one of claims 1 to 8, and performing extrusion and casting to form a film. 10.LECO battery single glass component, characterized in that: The invention comprises the highly reflective black packaging adhesive film as claimed in any one of claims 1 to 8.

Citation Information

Cited By

  • Spectral selective black photovoltaic packaging adhesive film as well as preparation method and application thereof

    CN121895883A

  • High-reflection black photovoltaic packaging adhesive film, preparation method thereof and photovoltaic module

    CN121930741A

  • Highly reflective black photovoltaic encapsulant film, method of making and photovoltaic module

    CN121930741B